Pembentukan Gelas Keramik Litium Alumina Silikat (LAS) dari Zeolit Penjerap Radionuklida Pb21° (Lithium Aluminium Silicate Glass Ceramic Forming From Zeolite Used As Pb21° Radionuclide Adsorber). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Some radioactive is classified according to radiotoxicity per unit activity. Pb21° is classified as high toxicity radionuclide so waste contains this radionuclide should be handled carefully. Natural Izeolite is widely used in adsorption processes. The zeolite is used to adsorb hazardous material such as radionuclide, and then it is proceeded further to form glass-ceramic. Natural zeolite contains basic oxides for farming glass, therefore it can be used as a raw material for